Data on a new beta titanium alloy system reinforced with superlattice intermetallic precipitates - Knowles,A; Tea-Sung,J; Bhowmik,A; Jones,N; Britton,TB; Giuliani,F; Stone,H; Dye,D (Data in Brief, 2018)
The data presented in this article are related to the research article entitled “a new beta titanium alloy system reinforced with superlattice intermetallic precipitates” (Knowles et al., 2018) [1]. This includes data from the as-cast alloy obtained using scanning electron microscopy (SEM) and x-ray diffraction (XRD) as well as SEM data in the solution heat treated condition. Transmission electron microscopy (TEM) selected area diffraction patterns (SADPs) are included from the alloy in the solution heat treated condition, as well as the aged condition that contained < 100nm B2 TiFe precipitates [1], the latter of which was found to exhibit double diffraction owing to the precipitate and matrix channels being of a similar width to the foil thickness (Williams and Carter, 2009) [2]. Further details are provided on the macroscopic compression testing of small scale cylinders. Of the micropillar deformation experiment performed in [1], SEM micrographs of focused ion beam (FIB) prepared 2µm micropillars are presented alongside those obtained at the end of the in-situ SEM deformation as well as videos of the in-situ deformation. Further, a table is included that lists the Schmidt factors of all the possible slip systems given the crystal orientations and loading axis of the deformed micropillars in the solution heat treated and aged conditions.